The medea hypothesis : is life on earth ultimately self-destructive? - Ward, Peter D. (Peter Douglas), 1949- (Science essentials (National Academy of Sciences (U.S.)), 2009)
In The Medea Hypothesis, renowned paleontologist Peter Ward proposes a revolutionary and provocative vision of life's relationship with the Earth's biosphere--one that has frightening implications for our future, yet also offers hope. Using the latest discoveries from the geological record, he argues that life might be its own worst enemy. This stands in stark contrast to James Lovelock's Gaia hypothesis--the idea that life sustains habitable conditions on Earth. In answer to Gaia, which draws on the idea of the "good mother" who nurtures life, Ward invokes Medea, the mythical mother who kille